Tasawuf, Identitas dan Kesehatan Mental: Memahami Manfaat Psikososial dari Ritual Sufi - Imel Lee Sensia; Khodijah (IAI Miftahul Ulum Pamekasan, 2025)
Psychosocial factors play a crucial role in an individual's mental health. With the rapid advancement of technology, many young people today are influenced in ways that affect their mental health. This paper aims to discuss Sufism and mental health through Sufi rituals. The research method employs a descriptive and qualitative approach using literature studies through secondary data. From the results of the literature review, which involved in-depth exploration and reading of various writings on Sufism, mental health, and Sufi rituals, the findings indicate that addressing mental health through Sufi rituals can have a healing effect. This belief is not only held by Sufi practitioners but is also increasingly embraced by the general public. A person's mental condition can be influenced by many factors, and maintaining mental health is crucial. The therapies present in Sufi rituals are accessible to individuals with any mental condition, allowing them to gradually discover their identity as religious beings in need of their Creator. Sufism is a way for individuals to approach their God, When an individual is close to God, their mental health will indirectly be in good condition, and they will feel at peace in facing various pressures in life.